Subthreshold repetitive transcranial magnetic stimulation suppresses ketamine-induced poly population spikes in rat sensorimotor cortex - Jiang, Wenxuan; Isenhart, Robert; Sutherland, Robert; Lu, Zhouxiao; Xu, Huijing; Pace, John; Bonaguidi, Michael A.; Lee, Darrin J.; Liu, Charles Y.; Song, Dong (Frontiers in Neuroscience, 2022)
Cortical oscillations within or across brain regions play fundamental roles in sensory, motor, and memory functions. It can be altered by neuromodulations such as repetitive transcranial magnetic stimulation (rTMS) and pharmacological manipulations such as ketamine. However, the neurobiological basis of the effects of rTMS and ketamine, as well as their interactions, on cortical oscillations is not understood. In this study, we developed and applied a rodent model that enabled simultaneous rTMS treatment, pharmacological manipulations, and invasive electrophysiological recordings, which is difficult in humans. Specifically, a miniaturized C-shaped coil was designed and fabricated to deliver focal subthreshold rTMS above the primary somatosensory (S1) and motor (M1) cortex in rats. Multi-electrode arrays were implanted to record local field potentials (LFPs) and single unit activities. A novel form of synchronized activities, poly population spikes (PPS), was discovered as the biomarker of ketamine in LFPs. Brief subthreshold rTMS effectively and reversibly suppressed PPS while increasing the firing rates of single unit activities. These results suggest that ketamine and rTMS have convergent but opposing effects on cortical oscillations and circuits. This highly robust phenomenon has important implications to understanding the neurobiological mechanisms of rTMS and ketamine as well as developing new therapeutic strategies involving both neuromodulation and pharmacological agents.